Evaluation of Density and Viability of Arbuscular Mycorrhizal Spores in Austrocedrus chilensis Forests Affected by Wildland Fires in Patagonia, Argentina - Salgado Salomón, María Eugenia (2025)
Simple SummaryWildfires represent a recurrent disturbance in the Andean Patagonia region, with increasingfrequency in recent decades. This study analyzed how fires could affect the density ofarbuscular mycorrhizal spores in forests of Austrocedrus chilensis, an endemic arbuscularmycorrhizal conifer vulnerable to fire. Our study area was settled in a widespread areaaffected by wildfire, with varying severities, in February 2015. Soil samples were collectedfrom three sites with different precipitation ranges and three different fire severities each,evaluated 10 months and 5 years after the fire. Our key findings were as follows: (a)post-fire, spores were significantly more abundant in sites affected by moderate severityfires than in unburned sites or those with high fire severity; (b) after 5 years, burned sitesshowed no differences between severities, but the driest sites showed no changes, since firesoccurred with the same pattern and spore density; (c) seedlings from the bioassay showedless than 25% mycorrhizal colonization in burned sites; (d) wildfires reduce arbuscularmycorrhizal spores and alter soil properties; (e) in drier sites, natural recovery is limited,requiring active restoration. Post-fire management must consider that wildfires reducemycorrhizal presence and alter soil properties.